Desarda's Tissue Repair Versus Lichtenstein Tension-Free Mesh Repair In The Treatment Of Primary Inguinal Hernia: A Cross-Sectional Observational Single-Institutional Study (International Journal of Environmental Sciences, 2025)
Inguinal hernias, which affect around 27% of men and 3% of women during their lifetime, constitute one of the most frequently treated surgical conditions [1]. Hernias arise when tissue, usually intestinal, bulges through a vulnerable area in the abdominal muscles, resulting in discomfort, pain, and potential complications if left untreated [2]. Surgical intervention remains the definitive treatment, with various techniques available, which can be broadly categorized into tissue repair and mesh-based repair methods [3].